2016
DOI: 10.1111/modl.12320
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Support Verb Constructions in Written Spanish Learner Corpora

Abstract: This article studies the use of support verb constructions (SVCs) in the written production of learners of Spanish. SVCs are lexical combinations whose content is similar to verbal predicates but is distributed between a verb and a noun, the noun being the carrier of the core lexical meaning of the predicate. Although there is considerable agreement on the importance of these constructions in the learning process, their use in the production of learners of Spanish has so far attracted little attention. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
3
2
0
3
Order By: Relevance
“…This finding confirms those of Salido (2016), obtained in an error analysis of 'Support Verb Constructions' (svcs) in written Spanish learner corpora. This study maintained that one of the most frequently collocation types used correctly and incorrectly in the corpus was that of svcs.…”
Section: Interference Errorssupporting
confidence: 90%
See 1 more Smart Citation
“…This finding confirms those of Salido (2016), obtained in an error analysis of 'Support Verb Constructions' (svcs) in written Spanish learner corpora. This study maintained that one of the most frequently collocation types used correctly and incorrectly in the corpus was that of svcs.…”
Section: Interference Errorssupporting
confidence: 90%
“…Here all-purpose forms, such as have, get, or a lot, were shown to be used in contexts where native speakers chose a word more specific to the collocation, such as acquire, undergo or profusely. This reflects Salido's (2016) findings in his study of support verb constructs, referred to above; Salido noted that svcs were common in both correct and incorrect collocations in learner language. A study of core words in coryl might involve searching for the word itself, for example get, and finding which words it tends to collocate with.…”
Section: Interlanguage Analysissupporting
confidence: 71%
“…Во-вторых, по результатам исследований многие коллокации, произведенные учениками, являются нестандартными: от приблизительно 20% по данным (Garcia Salido 2014;Benigno, Vedder 2016; Wang 2016) до более 30% по результатам (Nesselhauf 2004;Laufer, Waldman 2011). Самой распространенной ошибкой является выбор неправильного глагола (Nesselhauf 2004;Gilquin 2007;Laufer, Waldman 2011;Garcia Salido 2016;Wang 2016). Значительная часть нарушений в глагольно-именных кол-локациях вызвана трансфером с родного языка (Altenberg, Granger 2001;Nesselhauf 2005;Gilquin 2007;Juknevičienė 2008;Laufer, Waldman 2011;Scinetti 2013;Benigno, Vedder 2016).…”
Section: корпусные исследования конструкций с опорным глаголом в речи...unclassified
“…Значительная часть нарушений в глагольно-именных кол-локациях вызвана трансфером с родного языка (Altenberg, Granger 2001;Nesselhauf 2005;Gilquin 2007;Juknevičienė 2008;Laufer, Waldman 2011;Scinetti 2013;Benigno, Vedder 2016). Кроме отрицательного трансфера с L1, материал исследований свидетельствует о потенциальном положительном влиянии родного языка в случае полностью эквивалентных коллокаций (Kaszubski 2000;Nesselhauf 2005;Gilquin 2007;Scinetti 2013;Benigno, Vedder 2016;Garcia Salido 2016;Wang 2016). Другие ошибки являются интралингвистическими и обусловлены, например, нарушением принципа лексической связанности (Howarth 1996;Nesselhauf 2005; Wang 2016).…”
Section: корпусные исследования конструкций с опорным глаголом в речи...unclassified
“…Copying the meaning and form from one language to another results in a literal translation, which can be of the svc type. The study of support verb constructions is a concern not only in minority language settings (Backus and Dorleijn, 2009;Otheguy, 1993) but also in the domain of second language acquisition and pedagogical materials design since the accurate selection of the collocate verb can be difficult for learners and is very often subject to interlingual transfer, even among advanced language learners (Salido, 2016). In a study of verb+NP collocation errors made by Hebrewspeaking learners of English, Laufer and Waldman (2011) found that nearly 90% (42/47) of the error types in svc s that persisted from basic to advanced levels of L2 proficiency were direct translations of their semantically equivalent Hebrew collocations.…”
Section: 1mentioning
confidence: 99%